2009
DOI: 10.1093/jxb/erp036
|View full text |Cite
|
Sign up to set email alerts
|

Role of mesophyll diffusion conductance in constraining potential photosynthetic productivity in the field

Abstract: Limited mesophyll diffusion conductance to CO(2) (g(m)) can significantly constrain plant photosynthesis, but the extent of g(m)-limitation is still imperfectly known. As g(m) scales positively with foliage photosynthetic capacity (A), the CO(2) drawdown from substomatal cavities (C(i)) to chloroplasts (C(C), C(i)-C(C)=A/g(m)) rather than g(m) alone characterizes the mesophyll diffusion limitations of photosynthesis. The dependencies of g(m) on A, foliage structure (leaf dry mass per unit area, M(A)), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
221
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(237 citation statements)
references
References 173 publications
(202 reference statements)
10
221
2
4
Order By: Relevance
“…Thus, our results suggest a profound effect of g m on ı 13 C, as proposed by Barbour et al (2010). The inclusion of g m in process-based models of terrestrial vegetation may therefore improve the modeling of regional carbon and water fluxes under projected climate change (Niinemets et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
“…Thus, our results suggest a profound effect of g m on ı 13 C, as proposed by Barbour et al (2010). The inclusion of g m in process-based models of terrestrial vegetation may therefore improve the modeling of regional carbon and water fluxes under projected climate change (Niinemets et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
“…The drawdown of CO 2 from substomatal cavities to chloroplasts may reduce photosynthesis by 25-75%, depending on species (32). Differences in g m may even have the potential to alter the balance in species competitiveness as plant communities respond to rising atmospheric CO 2 because an atmosphere enriched in CO 2 may favor species with lower g m such as needleleaf evergreen trees and others (2,6). Thus, mesophyll diffusion can play a crucial role in our understanding and predicting photosynthetic responses to the increase in atmospheric CO 2 concentration from leaf to global scales.…”
Section: Resultsmentioning
confidence: 99%
“…However, diffusion of CO 2 through liquids is several orders of magnitude slower than it is through gases; diffusion through lipids in membranes is even slower than it is through liquid water (3), although it may be facilitated by aquaporin-like channels (4). Consequently, mesophyll layers constitute a major barrier for CO 2 movement inside leaves (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In conifers, the age-and size-dependent increase in LMA (LMA = leaf density × thickness) is primarily associated with enhanced leaf density, whereas both the thickness and density are increased in broadleaved species (England & Attiwill 2006, Juárez-López et al 2008, Niinemets et al 2009). Many studies have reported that agedependent (or size) increases in the LMA were possibly caused by greater water stress in the leaves of large trees (Ambrose et al 2009, Niinemets et al 2009). The photosynthetic capacity is also influenced by the increased LMA, and this effect has been related to changes in the ratios of internal air space and mesophyll area to the total area.…”
Section: Discussionmentioning
confidence: 99%